Opportunities and Challenges: Adopting “Blue-Green Economy” Terms to Achieve SDGs - Sungkawati, Endang (Revenue Journal: Management and Entrepreneurship, 2024)
Sustainable development and the blue-green economy are intimately linked and collaborate. Like other nations, Indonesia follows Blue-Green economic principles to reach the Sustainable Development Goals (SDGs). This study intends to investigate Indonesia's capacity and challenges in achieving the Sustainable Development Goals (SDGs) through implementing the Blue-Green economic concept and suggest solutions to address these barriers. Indonesia has adopted a substantial approach to attain sustainable development objectives by implementing a blue-green economic policy. This is primarily due to the country's status as a growing archipelago with a heightened susceptibility to natural disasters that affect all facets of society, the economy, and advancement. Indonesia is crucial in the global geopolitical scene because of its plentiful, untapped maritime resources. Implementing the Blue Economy in Indonesia offers a great chance to accomplish the 17 Sustainable Development Goals. Prior studies focused solely on the blue or green economy and strategies for attaining sustainable development goals in Indonesia. This research is innovative as it integrates the blue-green economic idea. The study discovered that obstacles can be surmounted by implementing solutions to address legislative, governance, legal, and economic challenges. Efficiently developing the public sector is crucial. This involves applying technology advancements, managing information effectively, coordinating with stakeholders, seeking international collaborations, and adopting global best practices. It aims to determine how sustainable development indicators, specifically in Indonesia, impact economic growth indicators such as gross domestic product. Time series analysis is utilized to depict the relationship between variables. The ARDL model research shows a long-term equilibrium relationship between different measures of sustainable development and economic growth in Indonesia. Indicators of sustainable development have been seen to influence economic growth in Iraq. The analysis demonstrates that sustainable development has fueled economic growth in Indonesia from 2014 to 2024.